2018
DOI: 10.1590/1518-8345.2744.3033
|View full text |Cite
|
Sign up to set email alerts
|

Sexual aspects of liver transplant candidates and recipients: evidence available in the literature

Abstract: Objective:to analyze the evidence available in the literature on the alterations in the sexuality of candidates and recipients of liver transplantation. Method:integrative review of the literature with search for primary studies in the databases MEDLINE (via PUBMED), CINAHL e LILACS, published in English, Portuguese and Spanish. Results:the 16 primary studies included were grouped into three categories: 1) female sexuality (n=5), 2) male sexuality (n=5) and 3) male and female sexuality (n=6). In category 1, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
(45 reference statements)
0
5
0
1
Order By: Relevance
“…27 It is known that satisfactory sexual health is fundamental for quality of life in transplanted patients; therefore, it cannot be disregarded during outpatient monitoring. 11 The improvement in the sleep pattern observed in this study can be related to reduction of the anxiety related to the disease and the expectation of undergoing the transplant, as well as the resolution of physiological conditions present in the disease in the initial post-transplant phase.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…27 It is known that satisfactory sexual health is fundamental for quality of life in transplanted patients; therefore, it cannot be disregarded during outpatient monitoring. 11 The improvement in the sleep pattern observed in this study can be related to reduction of the anxiety related to the disease and the expectation of undergoing the transplant, as well as the resolution of physiological conditions present in the disease in the initial post-transplant phase.…”
Section: Discussionmentioning
confidence: 51%
“…End-stage liver disease significantly reduces the patients' quality of life. 11 However, when liver transplant becomes the only option for chronic liver patients, although complex and expensive, it tends to enable physical, and psychological improvement in the patients. After transplantation, the patient needs to be monitored by a specialised multiprofessional team and to use of immunosuppressive medications throughout life, where their benefits outweigh the risks, and harms.…”
Section: Discussionmentioning
confidence: 99%
“…Evidencia-se que a função sexual é sensível à doença, ao sofrimento psicológico e ao desequilíbrio das relações interpessoais. Na maioria dos casos, a doença crônica é associada com a disfunção sexual, resultando na diminuição da atividade sexual em decorrência do mal-estar, da fadiga e de mudanças na imagem corporal (16) .…”
Section: Discussionunclassified
“…63% of this group requested more face‐to‐face guidance on the subject 2 . Similarly, adult kidney and liver transplant recipients also report high rates of sexual health concerns with ill‐preparation from their transplant providers 3‐8 …”
Section: Introductionmentioning
confidence: 99%
“…2 Similarly, adult kidney and liver transplant recipients also report high rates of sexual health concerns with ill-preparation from their transplant providers. [3][4][5][6][7][8] Transplant practitioners also report feeling underequipped to discuss aspects of sexual health reaching beyond teratogenicity of staple immunosuppressants. In a survey of 69 pediatric renal transplant nephrologists, Ashoor et al found that 67% felt comfortable counseling on safer sex, but less than half regularly discussed contraceptive options, unintended pregnancy, or provided specialist referrals for contraception.…”
mentioning
confidence: 99%